2022
DOI: 10.1111/jonm.13772
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of cultural intelligence between nurses' relationship conflict and teamwork

Abstract: Aims: To determine if there is a moderating effect of cultural intelligence between the conflict of nursing relationships and teamwork.Background: Relationship conflicts that exist in the nursing teamwork cannot be ignored. It would lead to poor teamwork and impact on patients' poor outcomes. In the meantime, cultural intelligence has been proven that people who have a higher cultural intelligence can do better at the work. Methods:The sample included 550 clinic nurses from five different hospitals in Shanghai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…A previous study examining the facets of nursing teamwork in multiple acute care environments observed a constant trend in NTS subdomains regardless of the nursing unit type [23], which is consistent with our findings. In addition, various studies have reported that NTS sub-domains have a moderateto-strong correlation with each other [14,38].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examining the facets of nursing teamwork in multiple acute care environments observed a constant trend in NTS subdomains regardless of the nursing unit type [23], which is consistent with our findings. In addition, various studies have reported that NTS sub-domains have a moderateto-strong correlation with each other [14,38].…”
Section: Discussionmentioning
confidence: 99%